Prevalencia de sobrepeso y obesidad en amas de casa de 20 - 60 años de edad del área urbana de la parroquia Cumbaratza. año 2015 - Pardo Cañar, Ketty del Carmen (2016)
The purpose of this research was to determine the prevalence of overweight and obesity in housewives of 20-60 year old urban area Cumbaratza parish in 2015. This corresponds to an epidemiological design where the types of research were used, transversal, descriptive, bibliographic, field. For data collection the questionnaire and the observation guide, survey applies as technical survey and observation instruments questionnaire and observation guide for data collection to 80 housewives of which 63 cases of overweight and obesity were determined. As a result it was found that the overall prevalence of overweight and obesity is 78.75%, obesity grade I stands with 50.79%. The grade I obesity has the highest prevalence with 17.46% at ages 30 to 39 followed by the group of 40-49 and 50-60 years with the 14.29% each, with 25.40% at the elementary level instruction reports the condition of obesity I degree, marital status reports the 23.81% each obese grade I. Depending on the number of children the prevalence of obesity grade I is for those who have one child with 14.29%, the predominate ethnic group is mestizo for overweight and obese, who consume diets rich in carbohydrates every day presented the 36.51% overweight. Protein consumption prevails obesity degree II and III in those who consume between 2-3 times a week. As a contribution educational activities, physical activity and nutritional care were implemented. In conclusion, the prevalence of overweight and obesity is high with predisposition mixed race ethnicity, married, aged 40 years, son, primary education, with the daily diet of carbohydrates which reported higher prevalence. Keywords. Prevalence, Overweight, Obesity, Housewives 20-60 Years